Learning/work : turning work and lifelong learning inside out - Cooper, Linda, 1953-; Walters, Shirley, 1949- (Cape Town, South Africa : HSRC Press, 2009)
"We are living through a daunting yet fascinating period in which th e global economy increasingly challenges the accepted dichotomies betwe en home-life and work-life, between employment and unemployment, paid w ork and unpaid work. This calls for serious analysis of how knowledge i s generated, both formally and informally, in workplaces as diverse as the factory, the field, or the street. It raises questions about what f orms of learning and training are involved; how they articulate with on e another and what practical and theoretical implications this has for our societies. In this book, 34 leading scholars from 10 countries chal lenge established understandings of lifelong learning and work, with se veral arguing that 'work' and 'lifelong learning' need to be 'urned ins ide out' through a rigorous critique of underlying social relations and practices so that we understand the power relations that shape learnin g/work possibilities. In various ways, all of the 25 chapters that make up this volume are infused with imaginings of alternative futures whic h prioritise social justice and sustainability for the majority in the world"--Publisher's website.
Includes bibliographical references and index.
Keywords: Continuing education -- Social aspects; Educational sociology; Adult learning